2007
DOI: 10.1128/iai.01660-06
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of CCL20 and Recruitment of CCR6+Gastric Infiltrating Lymphocytes inHelicobacter pyloriGastritis

Abstract: Helicobacter pylori infection is associated with an inflammatory response in the gastric mucosa, leading to chronic gastritis, peptic ulcers, and gastric cancer. There is increased T-cell infiltration at the site of infection with H. pylori. CCR6, a specific ␤-chemokine receptor for CCL20 (MIP-3␣/LARC/exodus), has recently been reported to mediate lymphocyte homeostasis and immune responses in mucosal tissue, and it may play a role in chemokine-mediated lymphocyte trafficking during gastric inflammation. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
67
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 40 publications
12
67
0
1
Order By: Relevance
“…In H. pylori-associated gastritis, recruitment of T-and B cells, dendritic cells and neutrophil granulocytes is mediated by a variety of chemokines interacting with their cognate receptors such as CCR7, CCR5, CXCR1 and CXCR4 expressed on infiltrating immunological cells. 30,[36][37][38][39][40][41] Consistent with these findings, we also observed upregulated mRNA transcripts of CCR8, CCR9, CXCR3 and CXCR7.…”
Section: Discussionsupporting
confidence: 90%
“…In H. pylori-associated gastritis, recruitment of T-and B cells, dendritic cells and neutrophil granulocytes is mediated by a variety of chemokines interacting with their cognate receptors such as CCR7, CCR5, CXCR1 and CXCR4 expressed on infiltrating immunological cells. 30,[36][37][38][39][40][41] Consistent with these findings, we also observed upregulated mRNA transcripts of CCR8, CCR9, CXCR3 and CXCR7.…”
Section: Discussionsupporting
confidence: 90%
“…H. pylori colonization induces systemic and mucosal immune responses (24). Bacterial colonization of the gastric mucosa triggers lymphoid infiltration (25) and the formation of acquired MALTs. H. pylori infection induces and sustains an actively proliferating B-cell population via direct and indirect immunologic stimulation and infiltrating T cells serve an important role in the development of MALT lymphomas (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…6,[8][9][10] It has been demonstrated that T helper type 1 cells selectively increased during H. pylori infection. [11][12][13][14][15] T helper type 1 cytokines, such as gamma interferon (IFN-c) and tumor-necrosis factor alpha (TNF-a), can increase the release of proinflammatory cytokines, augmenting apoptosis induced by H. pylori. 10 H. pylori infection could also induce gastric mucosa damage by increasing expression of Fas in gastric epithelial cells, leading to gastric epithelial cell apoptosis through Fas/FasL interaction with infiltrating T cells.…”
Section: Introductionmentioning
confidence: 99%